A Case of Facial Spasm Associated with Ipsilateral Cerebellopontine Angle Arachnoid Cyst - Ogawa, Hiroshi; Hiroshima, Satoru; Kamada, Kyousuke (The Surgery Journal, 2015)
The authors report a rare case of right cerebellopontine angle cyst related to hemifacial spasm. The patient was a 66-year-old woman with a 3-year history of right hemifacial spasm. The cyst was diagnosed preoperatively by T2-weighted magnetic resonance imaging, which demonstrated a hyperintense area in the right cerebellopontine angle. A small artery was displaced by the cyst and compressed the root exit zone of the facial nerve. Decompression of the cyst and the vasculature using a microsurgical technique resulted in total recovery from hemifacial spasm.
Keywords: cerebellopontine angle arachnoid cyst; hemifacial spasm; microvascular decompression